2011
DOI: 10.1007/s00425-010-1340-5
|View full text |Cite
|
Sign up to set email alerts
|

UV-B-induced DNA damage mediates expression changes of cell cycle regulatory genes in Arabidopsis root tips

Abstract: Even though a number of studies have shown that UV-B radiation inhibits plant growth and regulates the cell cycle progress, little is known about the molecular and cellular mechanisms. Here, we developed a synchronous root-tip cell system to investigate expression changes of cell cycle marker genes and DNA damage under UV-B radiation. Expression analysis of cell cycle marker genes revealed that G1-to-S transition in root-tip cells was accomplished within 6 h. In the in vivo synchronous root-tip cells, high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 65 publications
(59 reference statements)
2
37
0
Order By: Relevance
“…Different letters indicate statistically significant differences applying ANOVA test (P < 0.05). radiation were analyzed using actively dividing cells of Arabidopsis root tips (Jiang et al, 2011a). High levels of UV-B radiation induced expression changes of the cell cycle regulatory and DNA damage genes, suggesting that UV-B-induced DNA damage results in the delay of the G1-to-S transition of the cell cycle and that UV-B-induced G1-to-S arrest may be a protective mechanism that prevents cells with damaged DNA from dividing.…”
Section: Discussionmentioning
confidence: 99%
“…Different letters indicate statistically significant differences applying ANOVA test (P < 0.05). radiation were analyzed using actively dividing cells of Arabidopsis root tips (Jiang et al, 2011a). High levels of UV-B radiation induced expression changes of the cell cycle regulatory and DNA damage genes, suggesting that UV-B-induced DNA damage results in the delay of the G1-to-S transition of the cell cycle and that UV-B-induced G1-to-S arrest may be a protective mechanism that prevents cells with damaged DNA from dividing.…”
Section: Discussionmentioning
confidence: 99%
“…In our semi-quantitative RT-PCR assay, we found that Histone H4 expression was lower in 1376-CMIS than in 1376, indicating that cell-cycle arrest induced by SQ-1 in 1376 anthers was a consequence of DNA damage, and this regulation might be a response to DNA damage. In Arabidopsis, Histone H4 is downregulated by UV-B radiation, suggesting that UV-B-induced DNA damage results in a delay of the G1-to-S transition in plant cell cycles (Jiang et al, 2011). In addition, TaPCNA expression was higher in 1376-CMIS than in 1376 at all three stages.…”
Section: Discussionmentioning
confidence: 97%
“…Summary of morphogenic processes in uV-B exposed plants. uV-B can directly inhibit growth through cellular damage (Jiang et al, 2011). 27 alternatively, dwarfism is mediated through the uVr8 pathway (Favory et al, 2009) 18 , or uVr8 compensates for inhibitory effects of uV-B on growth (Wargent et al, 2009b).…”
Section: Underlying Cellular and Molecular Mechanismsmentioning
confidence: 99%
“…uV-B can directly inhibit growth through cellular damage (Jiang et al, 2011). 27 alternatively, dwarfism is mediated through the uVr8 pathway (Favory et al, 2009) 18 , or uVr8 compensates for inhibitory effects of uV-B on growth (Wargent et al, 2009b). 8 the uVr8 pathway may directly regulate morphogenesis, or this may involve crosstalk with other processes, including flavonoid accumulation, endoreduplication and antioxidant scavenging.…”
Section: Underlying Cellular and Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation